Gendered Language in Philippine Newspapers - Java, Almar (Journal of Interdisciplinary Perspectives, 2024)
Print media can influence public perceptions but may also reinforce gender bias through language. Numerous studies have underscored the persistence of linguistic sexism in print publications, highlighting how language choices can reinforce gender stereotypes and inequality. This study investigates gendered language in The Philippine Daily Inquirer, a leading newspaper in the Philippines, to highlight how sexist terms persist in modern print media. The study analyzed the May 2018 issue using quantitative and qualitative content analysis, focusing on terms influenced by Gender Schema Theory and Social Responsibility Theory. Five gendered terms with sexist undertones were identified: "policemen," "businessman," "countrymen," "gunmen," and "ombudsman," with "policemen" being the most common. These terms were grouped into three categories: Generic Masculine, Derogatory, and Pseudo-Masculine expressions, with Generic Masculine terms being the most prevalent. The findings show that print media continues to use sexist language, particularly through Generic Masculine terms. The study suggests a thorough content review in media outlets to remove sexist language and encourage gender-neutral alternatives.